Parents’ and teachers’ perspectives on children’s sexual health education: a qualitative study in Makwanpur Nepal - Acharya, Dev R; Thomas, Malcolm; Cann, Rosemary; Regmi, Pramod R (Health Prospect, 2019)
Sex education is taught to secondary school students in Nepal. Nevertheless, there are concerns that the school-based sexual health education is not effective and adequate to address young people’s necessities. We carried out a qualitative study comprising key informant interviews with teachers (n=8) and parents (n=6) in Makwanpur district in Nepal. Interviews were recorded, transcribed and translated into English. Thematic analysis was performed to identify patterns or themes within the qualitative data. Most participants (both teachers and parents) had thought of delivering sex education preferably from grade seven to avoid the effects of globalised mass media and the internet. The practical aspects of school sex education programme and the importance of parent-child communication were of major concerns. Comprehensive training to health teachers, an informal approach to teaching sex education and seeking outside health professionals, such as health facilitators were the frequently reported issues. There is a need to offer sexual health services along with sex education to protect young people from potential dangers of STIs including HIV infection. Particularly, health teachers should be trained properly to mitigate the social and cultural impacts, and to allow a smooth sex education discussion in the classroom. The curriculum for sex education should be relevant, engaging and developmentally suitable with clear progressive avenues for learning experience.